2001
DOI: 10.1111/j.1365-2842.2001.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular dysfunction in Turkish children with mixed and permanent dentition

Abstract: This study was carried out to determine the prevalence of temporomandibular joint (TMJ) dysfunction in mixed and permanent dentition and to evaluate the sex distribution in Turkish children. One hundred and eighty-two children with mixed dentition and 212 with permanent dentition were selected for the study, which used a questionnaire and clinical examination. Children with one or more signs (TMJ sounds, TMJ tenderness, muscle tenderness, restricted mouth opening) and/or symptoms (TMJ pain during mastication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
19

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 19 publications
3
31
1
19
Order By: Relevance
“…In this study, the frequency of 65% of TMD symptoms was similar to that found in other studies reported in literature, such as 63% (14) and 68% (15). However, other authors reported lower frequencies, varying from 3% to 50% (5,16-20).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the frequency of 65% of TMD symptoms was similar to that found in other studies reported in literature, such as 63% (14) and 68% (15). However, other authors reported lower frequencies, varying from 3% to 50% (5,16-20).…”
Section: Discussionsupporting
confidence: 91%
“…Literature indicates for example that prepubescent boys and girls display equal prevalence in the majority of chronic pain conditions. However, after the approximate age of 12 years, a female predominance is established up until menopause (characterized by gradually declining estrogen levels), where this prevalence thereafter declines (Abu-Arefeh and Russell, 1994; Bigal et al, 2007; Lipton et al, 2001; Ogura et al, 1985; Sonmez et al, 2001). Furthermore, pain sensitivity differences throughout the female menstrual cycle (Crawford et al, 2009; LeResche et al, 2003; Pamuk and Cakir, 2005) and the rodent estrous cycle (Frye et al, 1992; Giamberardino et al, 1997; Kayser et al, 1996) also indicate a role for gonadal hormones in chronic pain states, with higher levels of estrogens correlating with higher pain scores.…”
Section: A Role For Tlr4 In Enhanced Female Nociception?mentioning
confidence: 99%
“…Bu fizyolojik süreçler hastanın TME bölgesinde ciddi ağrı hissetmesine ve hareket kısıtlılığı ile karşılaşmasına yol açabilir 13 . Ön kesici dişler arası maksimum mesafe (ÖKDAMM) sağ-lıklı bireylerde 23-71 mm arası değişmekte ve TME kondil mobilitesinden etkilenmektedir 14 . Çalışmamız-da, adenoidektomi ve/veya tonsillektomi grubunda ameliyat sonrası ilk ÖKDAMM ortalama ölçümlerin-de düşüş görülmüştür.…”
Section: Discussionunclassified